Analysis Of Outside Claim Fragmentation On BPJS Claims In Hospital - Rahayu, Tiny; Rahma Tika, Mia; Lestariyowidodo, Sapta (Rifa'Institute, 2021)
The Social Security Organizing Agency (BPJS) has provisions regardingfraud in which one form of fraud is the breakdown of service episodes that are not in accordance with medical indications (serviceunbundling or fragmentation)it is done by health care providers in Health Facilities Referral Follow-Up (FKRTL) the action is done intentionally, to get financial benefits from public relations. Health Insurance program in the National Social Security System through fraudulent acts that are not in accordance with the provisions of the laws and regulations. The purpose of this study is to analyze the occurrence of Fragmentation in Hospital X. This research method uses quantitative methods from the data obtained. The results of this study of the Hospital conducted fragmentation in february 33 files and march 24 files and the number of fragmentation in mountax services. The hospital argued not to experience losses because the claim package that has been arranged by the Health Insurance Organizing Agency (BPJS) Instead of the Health Insurance Organizing Agency (BPJS) prohibits fragmentation because it includesfraud. In this study, the hospital can fragment because it is not applied standard operating procedures properly and in accordance with PERMENKES Number 16 of 2020 the hospital must have a fraud prevention team in order to conduct early detection.